Gambaran Kesehatan Jiwa Mahasiswa Keperawatan Pasca Pandemi COVID-19 - Widyo Subagyo; Dyah Wahyuningsih; Mukhadiono Mukhadiono (Jurnal Kesehatan Medika Udayana, 2023)
Background: The COVID-19 pandemic has had a major impact on mental health, including students. Symptoms that are quite dominant include not being able to think clearly, often feeling headaches, not sleeping well, easily feeling afraid, shaking hands, difficulty making decisions, easily tired and others. Students with mental health disorders are at risk of experiencing academic problems. Purpose: This study was to describe the mental health of nursing students after the Covid-19 pandemic. Method: The research design used is descriptive analytic with a cross sectional approach, which is a type of research where the measurement of the variables is only done once at a time. The research instrument for measuring students' mental health uses the Self-Report Questionnaire-20 (SRQ-20). The research population is level 1 nursing students in Purwokerto Nursing Study Program for the 2022/2023 academic year with a total of 133 students. The sampling technique used is total sampling. Result; Respondents on average were 18 years old, mostly female, 117 people (88.00%), owned computer equipment, mostly owned by 98 people (73.70%), parents' income was mostly around Rp. 2 million - Rp. 4 million, namely 65 people (48.90%) and experiencing distress, namely 70 people (52.60%). Conclusion; most nursing students after the Covid-19 pandemic experienced distress.